If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(j-6)+12=-16+4j
We move all terms to the left:
3(j-6)+12-(-16+4j)=0
We add all the numbers together, and all the variables
3(j-6)-(4j-16)+12=0
We multiply parentheses
3j-(4j-16)-18+12=0
We get rid of parentheses
3j-4j+16-18+12=0
We add all the numbers together, and all the variables
-1j+10=0
We move all terms containing j to the left, all other terms to the right
-j=-10
j=-10/-1
j=+10
| -4x+3=-x-27 | | v/8-4=4 | | 200+20x=1.98 | | 40t=28 | | 4m=5m-14 | | 5y-8=7-6 | | -10=2x+14 | | 2z+12=15 | | -2(u+6)=-4u-22 | | -19=-4-5m | | 180+x+(x-60)=360 | | -13.8=v/5-1.3 | | (2x+30)°=135 | | 2(4x+6)=-36+16 | | 140=7(-4-6x) | | 4000=50+32x | | -3v-7=-34 | | 9x+7=3(3x+5) | | g3+5=7 | | 3x6=-x-18 | | -3b-16b=19 | | 3-m/8=4-m/6 | | 35+7y=-35+2y | | -6-5x=79 | | 105=5x^2+25 | | 9x+7=3(3x+5 | | z+4(2z+3)=13 | | 2=3(y-2)-7y | | 5b^2+4b^2=360 | | 6(1+5b)+5=-109 | | 30=2+7n | | r4+ 11=15 |